Physiology of professional road cycling - Luci, A.; Hoyos, J.; Chicharro, J. L. (Sports Medicine, 2001)
Professional road cycling is an extreme endurance sport. Approximately 30000 to 35000 km are cycled each year in training and competition and some races, such as the Tour de France last 21 days (approximately 100 hours of competition) during which professional cyclists (PC) must cover >3500 km. In some phases of such a demanding sport, on the other hand, exercise intensity is surprisingly high, since PC must complete prolonged periods of exercise (i.e. time trials, high mountain ascents) at high percentages (approximately 90%) of maximal oxygen uptake (VO2max) [above the anaerobic threshold (AT)]. Although numerous studies have analysed the physiological responses of elite, amateur level road cyclists during the last 2 decades, their findings might not be directly extrapolated to professional cycling. Several studies have recently shown that PC exhibit some remarkable physiological responses and adaptations such as: an efficient respiratory system (i.e. lack of 'tachypnoeic shift' at high exercise intensities); a considerable reliance on fat metabolism even at high power outputs; or several neuromuscular adaptations (i.e. a great resistance to fatigue of slow motor units). This article extensively reviews the different responses and adaptations (cardiopulmonary system, metabolism, neuromuscular factors or endocrine system) to this sport. A special emphasis is placed on the evaluation of performance both in the laboratory (i.e. the controversial Conconi test, distinction between climbing and time trial ability, etc.) and during actual competitions such as the Tour de France.